Characteristics and outcomes of SARS‐CoV‐2 infection in Victorian children at a tertiary paediatric hospital. (25th October 2021) - Tosif, Shidan; Ibrahim, Laila F; Hughes, Rebecca; R Cheng, Daryl; Wurzel, Danielle; Overmars, Isabella; Steer, Andrew C; Bryant, Penelope A; Duke, Trevor; Lewena, Stuart; Babl, Franz E; McNab, Sarah; et al.
Abstract : Aim: Victoria experienced two 'waves' of COVID‐19 between March and September 2020 and more cases than any other jurisdiction in Australia. Although world‐wide reports of COVID‐19 reflect that children are less likely to experience severe disease compared with adults, hospitalisations and deaths have been reported. We report testing and outcomes of children with SARS‐CoV‐2 infection presenting to a tertiary paediatric hospital in Melbourne. Methods: We conducted a prospective cohort study at The Royal Children's Hospital (RCH), including all children and adolescents (aged 0–18 years) who presented and were tested for SARS‐CoV‐2 over a 6‐month period, between 21 March 2020, up to the 21 September 2020. Detailed epidemiological and clinical data were recorded. Results: A total of 19 708 tests for SARS‐CoV‐2 were performed in 14 419 patients. One hundred and eighty patients tested positive for SARS‐CoV‐2 (1.2%). 110 (61%) were symptomatic, 60 (33%) were asymptomatic and 10 (6%) were pre‐symptomatic. Close contacts of a positive case were associated with a higher risk of a testing positive for SARS‐CoV‐2 (120/2027 (6%) vs. 60/14589 (0.4%), RD 5.5 (95% CI 4.5 to 6.5), P < 0.001). Eighteen (10%) SARS‐CoV‐2‐positive patients were admitted to hospital with one patient requiring intensive care. All patients recovered fully with no deaths. Conclusion: In Victorian children presenting to a tertiary hospital, SARS‐CoV‐2 infection caused predominantly mild or asymptomatic infection, with most children not requiring hospitalisation.